ATTENTION DEFICIT HYPERACTIVITY DISORDER. A CLINICAL LECTURE - A. S. Kotov; M. N. Borisova; M. V. Panteleeva; Yu. V. Matyuk; A. V. Shatalin (Русский журнал детской неврологии, 2015)
Attention deficit hyperactivity disorder (ADHD) is a serious problem to pediatric neurologists. The prevalence of ADHD in developed countries ranges from 1 to 20 %. ADHD is characterized by a triad of symptoms: inattention, hyperactivity, and impulsivity (the International Statistical Classification of Diseases, 10th revision, codes it as F90) and it is the most common conduct disorder in children. The etiology of ADHD remains disсutable to the present day; there are a few basic concepts of the origin of this disorder. Its manifestations may be a reason for family conflicts, poor peer relationships, social and school maladjustment, learning problems, lower academic performance, accidents and injuries, smoking, psychoactive substance abuse (toxicomania, narcomania), delinquencies, deviant social behavior, thus having a negative impact on all spheres of a patient’s life. The manifestations of ADHD may continue in adulthood, resulting in work and family life problems, low self-evaluation, alcohol and psychoactive substance abuse, and other unfavorable consequences. The authors describe the etiology, pathogenesis, diagnostic principles (diagnostic scales and tests), differential diagnosis (by setting out a large group of different diseases, the manifestations of which can mimic ADHD), treatment, and prognosis of the disorder. Within its therapeutic correction framework, the authors present the definition and general principles of Montessori therapy, including recommendations for parents and relatives to deal with children with ADHD.